The Principle of Good Faith in Purchase Agreements for Land Ownership - YANTI, Ni Kadek Putri; WIJAYA , I Ketut Kasta Arya; AGUNG , Anak Agung Istri (Indonesia Strategic Sustainability, 2025)
This research examines the principle of good faith in the sale and purchase agreement of land ownership rights. In practice, there are occurrences of multiple sale and purchase agreements for land ownership rights. In this event, the seller conducted two binding sale and purchase agreements for land ownership rights with different buyers, resulting in losses for the first buyer. Based on this, the seller is deemed not to have acted in good faith in making the sale and purchase agreement. The research used in this study is normative legal research. The approaches used in this research are legislative approach, case approach, and conceptual approach. The sources of legal materials utilize primary legal materials and secondary legal materials. The technique for collecting legal materials used in this research is through library techniques and document studies, which are then qualitatively analyzed by providing descriptions related to the application of the principle of good faith in the sale and purchase agreement of land ownership. The principle of good faith in ownership sale and purchase agreements for land is regulated in Article 1338 paragraph (3) of the Civil Code. Additionally, it is also reflected in the provisions of Article 1320 of the Civil Code which governs the valid conditions of agreements. Furthermore, the legal consequences for the seller in a sales agreement that is not based on good faith are null and void by law because it contradicts the principle of good faith and does not meet the objective requirements for a valid agreement.